Illocutionary and Perlocutionary Acts Analysis of Ellen DeGeneres' Utterances in Talk Show - Kinasih, Sekar; Rido, Akhyar (TEKNOSASTIK, 2025)
This study aims to investigate the strategies employed by Ellen DeGeneres in using illocutionary acts during conversations on her talk show and examine the perlocutionary effects of her utterances on guests. Using Searle's speech act theory; the analysis focuses on Ellen DeGeneres' interactions with Michelle Obama and Portia de Rossi. This study uses a descriptive qualitative approach and collects the data through library research. The findings reveal that Ellen DeGeneres primarily used assertive illocutionary acts in her talk show, effectively fostering rapport and guest participation. Her assertive strategies include sharing personal experiences and factual statements, guided conversations, and eliciting cognitive and emotional perlocutionary effects, including reflection, agreement, and validation from Michelle and Portia. This study concludes that Ellen DeGeneres' assertive and directive speech acts were key in building rapport and guiding guest interactions, prompting cognitive and emotional responses. English Literature programs should include speech act theory, with workshops and role-play to help students learn and apply it in talk shows or interview simulations. Additionally, media professionals should undergo development programs focused on assertive and directive speech strategies for more dynamic and meaningful interactions.Keywords: Assertive strategies, Illocutionary act, Perlocutionary act, Speech act theory